Evaluation of therapeutic agent selection based on comprehensive genomic profiling in gastroenteropancreatic neuroendocrine neoplasms - Miyazawa, Suguru; Ono, Hiroaki; Yamashita, Hironari; Asano, Daisuke; Ishikawa, Yoshiya; Watanabe, Shuichi; Ueda, Hiroki; Aoyama, Satoru; Ishibashi, Naoya; Akahoshi, Keiichi; Ikeda, Sadakatsu; Tanabe, Minoru (PloS one, 2025)
Comprehensive genomic profiling (CGP) is increasingly being integrated into standard clinical practice as a strategy to guide subsequent treatment decisions by identifying novel therapeutic options based on tumor-specific mutations. However, its clinical utility in neuroendocrine neoplasms (NENs) remains to be determined. We conducted a cross-sectional analysis of genomic alterations, including tumor mutational burden (TMB) and microsatellite instability (MSI), in gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs), comparing neuroendocrine tumors (NETs) and neuroendocrine carcinomas (NECs). CGP was performed on 50 patients with advanced GEP-NENs between August 2017 and October 2023. Of these, 38 were diagnosed with NETs and 12 with NECs. Primary tumor sites included the pancreas (n = 24), gastrointestinal tract (n = 25), and one case of unknown origin. In our study, CGP analysis comparing NETs and NECs documented different genetic profiles. In addition, median TMB was significantly higher in NECs (5.0 vs. 1.9 mutations/megabase; p = 0.0101). High TMB was identified in 4 of 12 NECs (33.3%) and in only 1 of 38 NETs (2.6%) (p = 0.0093). NECs also harbored a significantly greater number of mutations per case than NETs (5.5 vs. 2.0; p = 0.0014). Actionable mutations were identified in 18 of 50 patients, and 7 patients received mutation-guided therapy: 2 with NETs and 5 with NECs. The frequency of treatment initiation based on CGP findings was significantly higher in patients with NECs (p = 0.0059). NECs are genetically distinct from NETs, with a higher prevalence of actionable mutations and greater therapeutic relevance of CGP findings. These results suggest that CGP may be particularly valuable in NECs, where therapeutic options are limited, supporting its proactive implementation in this subgroup.